Effect of bioadhesion on initial in vitro buoyancy of effervescent floating matrix tablets of ciprofloxacin HCL - Jeetendra Singh Negi; Abhinav Trivedi; Praveen Khanduri; Vandana Negi; Nikhil Kasliwal (Wolters Kluwer Medknow Publications, 2011)
The purpose of this study was to investigate effect of bioadhesion on the initial in vitro buoyancy behaviour of effervescent matrix tablets of ciprofloxacin HCl (CIPRO). Tablets were prepared by direct compression using HPMC K4M and Carbopol 971P as hydrophilic-controlled release polymers, sodium bicarbonate (NaHCO 3 ) as gas-generating agent, polyplasdone XL, Explotab and Ac-Di-Sol as swelling agents. Tablets were evaluated for normal and modified initial in vitro floating behavior, floating duration, swelling behavior and in vitro drug release studies. A modified buoyancy lag time for tablets was determined in order to include the effect of bioadhesion on initial buoyancy. The initial buoyancy was found depended on bioadhesion ability of tablets. The lowest modified buoyancy lag time of 20 seconds was obtained for Formulation F7 having both NaHCO 3 and polyplasdone XL. The floating duration was also found dependent on concentration of NaHCO 3 and swelling agents. The drug release of F7 was also sustained up to 12-hr duration with anomalous drug transport mechanism.